(untitled) (Advances in Applied Mathematics and Mechanics, 2019)
In this paper, Lagrangian tracking of a specific material surface and Lagrangian-averaged vorticity deviation (LAVD) are applied to experimental data sets of two kinds of wall-bounded flows to detect coherent structures. One is used for laminar boundary layer with wall-mounted hemisphere, the other is used for turbulent boundary layer. Lagrangian coherent structures detected in a hemisphere protruded laminar boundary layer show some similarity with Eulerian-detected hairpin vortices. However, the LAVD-based vortices and the evolution of material surface demonstrated in turbulent boundary layer are different from the patterns in the wake of the hairpin shedding hemisphere. The wavelike deformed material surfaces appear to support the importance of three-dimensional wave structures in the near-wall turbulence production process. The Lagrangian methods provide another perspective in understanding coherent structures in wall-bounded flows.